Uncommon Lymphoepithelial Cyst with Sebaceous Glands of the Pancreas - Nakamura, Tsukasa; Osaka, Yoshio; Ishikawa, Shoichi; Sako, Hirotaka; Akamatsu, Naoaki; Yamamoto, Yoshihiro; Hosokawa, Yohei; Yoshimura, Norio (JOP. Journal of the Pancreas, 2013)
Context Lymphoepithelial cysts with sebaceous glands of the pancreas are extremely rare, with only 7 cases, including this case, published in English literature. Case report We herein present the case of a 67-year-old Asian man who underwent a resection of a lymphoepithelial cyst of the pancreas during the follow up care for lung cancer. Fourteen years previously he underwent a right lower lobectomy at the right segment nine for lung cancer. A 20 mm mass in the body of the pancreas was identified by CT scan 4 years ago, and the diagnosis was intraductal papillary mucinous neoplasm (IPMN) at that time. Over a 5-year period, this mass grew to 42 mm without dilatation of the main pancreatic duct. The preoperative evaluation, including endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA), indicated a cystic neoplasm with suspicion of malignancy. Intraoperative frozen section revealed a squamous-lined cyst accompanied by sebaceous glands without any malignant findings. Following this pathological finding, resection of the cyst was performed. Consequently, microscopic examination revealed that it was a lymphoepithelial cyst with sebaceous glands of the pancreas. Conclusions Pancreatic lymphoepithelial cysts can be cured by conservative resection, but if they are asymptomatic and are diagnosed before surgery, no treatment is necessary. To our knowledge, this is the first ever published case of a lymphoepithelial cyst with sebaceous glands of the pancreas, which was found during the follow up care for lung cancer. Image: Cysts enveloped by a fibrotic capsule.